A RODA DA VIDA - Silva, Lenina Lopes Soares (Revista Kairós-Gerontologia, 2010)
KÜBLER-ROSS, Elisabeth (1998). A roda da vida: memórias do viver e do morrer. Tradução de Maria Luiza Newlands Silveira. Rio de Janeiro, GMT.